It takes a village: an interview with Willias Masocha on the importance of networking in science (Nature Portfolio, 2021)
Willias Masocha is a Professor in the Department of Pharmacology & Therapeutics at Kuwait University where he studies the pathophysiology and treatment of neuropathic pain. Professor Masocha obtained a Bachelor of Pharmacy Honours from the University of Zimbabwe followed by a PhD in Pharmacology at the University of Granada before undertaking his postdoctoral training and International Brain Research Organization (IBRO) fellowship at the Karolinska Institutet. He began his independent research career at Kuwait University in 2006. In this Q&A he tells us about his current work and his perspectives on neuroscience research in the Middle East and Africa. He also shares tips for young scientists—particularly those based in Africa.